Utility of paperless partogram in labor management - Tarannum, Nazli; Akhtar, Nishat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Partograph use in labor has revolutionized the obstetric care. WHO recommends universal use of WHO modified partograph, which in clinical setup is less often used. Debdas (2006) proposed the paperless partogram which is designed for use by clinician/nurses/midwives as it is very simple and low skill method. The present study is proposed to evaluate the effectiveness of paperless partogram as a bedside tool and its comparison with WHO modified partograph. Methods: It was a prospective analytical study done in department of obstetrics and gynecology, JNMCH, AMU, Aligarh from September 2017 to July 2019 and included 400 pregnant women at term, divided into 2 groups of 100 each Group A (paperless partogram) and Group B (WHO modified partograph) and their labor events were followed. Results: Out of 200 women that were included in each group, maximum women were multigravida, 58.5% in group A and 61.5% women in Group B. Mean age in Group A was 24.68±3.8years and Group B was 24.93±3.75 years. The mean duration of labor in Group A was 3.57±2.20 hours and Group B was 3.40±2.03 hours. There were 87.5% of women who delivered before alert ETD, likewise in Group B; women who delivered before alert line are 88.5%. These differences were statically not significant. Perinatal outcome was also similar in both groups. Conclusions: In our study, the paperless study was found to be as efficient as WHO modified partograph for management of labor. The mean delivery time was 3.57 hours similar to WHO partograph of difference between alert and action line. Thus, for resource poor setting like India with overburdened population paperless partogram can be used as an alternative to WHO modified partograph which is complex and time consuming.